Risk Hazard Identification Using the HIRARC Method in the Construction of the KAI Boutique Hotel Cihampelas Building - Bandung - Bubung Burhanudin; Rifky Budiman; Muslim Rafiz; Fathur Rohman Robandi (Riviera Publishing, 2024)
Construction projects involving heavy equipment, work at heights, and hazardous conditions are inherently high-risk, making safety management crucial. This study identifies hazards related to work accidents at the KAI Boutique Hotel Cihampelas project using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method. The research applies a mixed-method approach, combining site observations, interviews, and questionnaires with project stakeholders. Statistical analysis and risk mapping classify risks based on severity and probability. Findings reveal 29 identified risks across ten work categories, including six high-risk items, 20 medium-risk items, and three low-risk items. The study emphasizes the need for consistent safety measures such as protective equipment, safety training, and adherence to standard procedures. The research’s novelty lies in its tailored HIRARC application in a specific construction context, offering actionable insights into mitigating occupational hazards and enhancing site safety.